Efficacy and safety of neoadjuvant systemic therapy in resectable hepatocellular carcinoma: a Systematic Review and meta-analysis - Wu, Dongdong; Liu, Ning; Dong, Hao; Zhou, Kan; Du, Lei; Li, Ying; Chao, Yanjun; Ma, Fuping (Frontiers in Oncology, 2025)
BackgroundNeoadjuvant systemic therapy has been shown to benefit patients with solid tumors such as breast cancer and colorectal cancer, but its application in hepatocellular carcinoma (HCC) is still in the exploratory stage, with no established effective regimen. This systematic review and meta-analysis aims to investigate the efficacy and safety of neoadjuvant systemic therapy in patients with resectable HCC.MethodsThe clinical trials of resectable HCC neoadjuvant systemic therapy in PubMed, Embase and the Cochrane Library were systematically searched. A meta-analysis was performed using STATA/MP18.0 software, and the effect size was calculated using either a fixed effects model or a random effects model, and 95% confidence intervals (CIs) were calculated. Subgroup analysis was performed according to the neoadjuvant systemic therapy regimen.ResultsThis meta-analysis included 328 patients from 15 studies. In patients with resectable HCC, the pooled pathologic complete response (pCR) rate was 15% (95%CI: 10%–21%), the major pathologic response (MPR) rate was 28% (95%CI: 21%–35%), the incidence of grade 3–4 treatment-related adverse events (TRAEs) was 11% (95% CI: 4%–20%), the objective response rate (ORR) was 27% (95% CI: 20%–35%), the surgical resection rate was 84% (95%CI: 75%–92%), and the delay rate was 0.00% (95% CI: 0%–4%). The results of subgroup analysis showed that the efficacy of targeted therapy combined with immunotherapy is superior to dual ICI (immune checkpoint inhibitor) combination therapy and ICI monotherapy, while the safety of the ICI monotherapy was the highest, superior to the dual ICIs and the targeted therapy combined with immunotherapy.ConclusionNeoadjuvant systemic therapy shows preliminarily beneficial outcomes in resectable HCC treatment. However, future large-scale and multicenter randomized controlled trials are needed to confirm this conclusion.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024562257